Kulturni genom Prostor in njegovi ideogrami mitične zgodbe - Pleterski, Andrej (Studia Mythologica Slavica Supplementa, 2014)
[The cultural genome.Space and its ideograms of the mythical story]As a biological genome determines our biological appearance, so too the cultural genome determines our cultural expression. This is a set of findings about the functioning of the universe and rules derived from them. When people verbalize these findings in a narrative, a mythical story occurs. A mythical landscape is a form of the cultural landscape that people created in accordance with their mythical conceptions that they could master the forces of nature with its help. From individual structures of the text fragments of Slavic folk traditions, a composite story in many versions is made, which explains the mechanism of renewal and describes the cyclical changes of the nature. People were using this mythical story as a mental model, which was materialized in specific spaces as spatial ideograms, which are discussed in the next part of the book ('The cultural genome. Space and its ideograms of the mythical story').